Designers' guide to Eurocode 8 design of bridges for earthquake resistance, EN 1998-2 - Kolias, Basil (ICE, 2012)
This guide focuses specifically on EN 1998-2 (Eurocode 8. Part 2 Bridges), the design standard for use in the seismic design of bridges in which horizontal seismic actions are mainly resisted through bending of the piers or at the abutments; however it can also be applied to the seismic design of cable-stayed and arched bridges.
Keywords: Bridges -- Earthquake effects -- Standards -- Europe.; Bridges -- Design and construction -- Standards -- Europe.; Structural design -- Standards -- Europe.; elektronické knihy; electronic books